INTEGRATION OF PRIMARY CARE AND SPECIALIZED NETWORK: INTERDISCIPLINARITY, EQUITY, AND CHALLENGES IN THE CARE OF CHRONIC DISEASES - Peixoto Ferreira de Souza, Leandro; Aparecida de Moura Sagário, Franciele; Laura Maciel de Melo, Anna; Fabíola Silva Araújo, Mayonara; Andreza de Arruda, Marília (Revista Gênero e Interdisciplinaridade, 2026)
Noncommunicable chronic diseases (NCDs) pose complex challenges to the organization of health systems, especially within Brazil’s Unified Health System (SUS). Primary Health Care (PHC), recognized as the coordinator of care, plays a strategic role in integrating with Specialized Outpatient Care (SOC) to ensure continuity and comprehensiveness of care. This qualitative narrative review aims to critically analyze the articulation between PHC and SOC in the care of NCDs, based on studies published from 2022 to 2025. The analysis is structured into thematic axes: planning and organization of specialized services; coordination of care by PHC; continuing education and interprofessional practices; use of technologies and information systems; and regional governance. The findings indicate that, despite conceptual advances with the Chronic Conditions Care Model (MACC) and Health Care Planning (PAS), structural, technical, and political barriers still hinder effective integration between levels of care. Service fragmentation, lack of shared clinical protocols, and low interoperability of information systems hinder care continuity. It is concluded that integration depends on broad institutional changes, appreciation of interprofessionalism, strengthening of PHC, and investment in collaborative regional management. The study contributes to reflections on possible paths toward more integrated, humanized, and resolutive health care networks.